2015
DOI: 10.1261/rna.053397.115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of autosomal-dominant retinitis pigmentosa in Caenorhabditis elegans uncovers a nexus between global impaired functioning of certain splicing factors and cell type-specific apoptosis

Abstract: Retinitis pigmentosa (RP) is a rare genetic disease that causes gradual blindness through retinal degeneration. Intriguingly, seven of the 24 genes identified as responsible for the autosomal-dominant form (adRP) are ubiquitous spliceosome components whose impairment causes disease only in the retina. The fact that these proteins are essential in all organisms hampers genetic, genomic, and physiological studies, but we addressed these difficulties by using RNAi in Caenorhabditis elegans. Our study of worm phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Partial loss-of-function of prp-6 causes misregulation of several 100 genes, including the cadherin cdh-5 . 11 We found that overexpression of cdh-5 can partially suppress axonal defects in cdh-4 mutants, suggesting that cdh-5 can partially compensate for the loss of cdh-4 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Partial loss-of-function of prp-6 causes misregulation of several 100 genes, including the cadherin cdh-5 . 11 We found that overexpression of cdh-5 can partially suppress axonal defects in cdh-4 mutants, suggesting that cdh-5 can partially compensate for the loss of cdh-4 .…”
Section: Introductionmentioning
confidence: 60%
“…This confirms that the suppression of axonal defects is caused by a mutation in prp-6 . Complete loss-of-function of prp-6 is lethal, 11 since splicing is an essential cellular process. Therefore, prp-6(hd170) is likely to be a partial loss-of-function allele.…”
Section: Resultsmentioning
confidence: 99%
“…We chose PRPF8 and SNRNP200 because these two proteins physically interact through the C-terminal region of PRPF8, where the s-adRP mutations are located (10). Moreover, RNAi of their orthologs in C. elegans, along with PRPF6, showed the most penetrant phenotypes (26). These three genes encode proteins of the U5 complex and, based on our previous RNAi experiments, would be more prone to harbor missense mutations with a strong phenotype than the other three splicing factors (PRP3, PRPF31 and PRPF4), which are part of the U4 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Such extraordinary conservation would imply maintenance of the function and therefore the missense mutations could have similar consequences at the molecular level in humans and in nematodes. C. elegans has already been exploited as model for s-adRP (26) and would be further exploited in the future if functional replacement of C. elegans s-adRP genes at its endogenous locus can be achieved with their human counterparts. The challenge here would be to express a functional human splicing factor at endogenous levels without causing any phenotype in the nematode.…”
Section: Discussionmentioning
confidence: 99%
“…These seven genes are PRPF3, PRPF4, PRPF6, PRPF8, PRPF31, SNRNP200 and RP9. All of them, except for RP9, encode highly conserved proteins between C. elegans and humans [114]. Photoreceptor cells are characterized by an intense transcriptional activity and metabolic rate [115] and, even though they are absent in C. elegans, the animal does present other cells that have similar increased metabolic rate and high transcriptional levels during the larval phase [116,117].…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%